Suitability of Tillandsia usneoides and Aechmea fasciata for biomonitoring toxic elements under tropical seasonal climate - Giampaoli, Patricia (2016)
Aechmea fasciata was evaluated for the ﬁrst time as a biomonitor of toxic elements, in comparison to thebiomonitoring capacity of Tillandsia usneoides, a well-established biomonitor bromeliad species. Plants of both species were exposed to air pollutants from industrial, urban, and agricultural sources, under the tropical seasonal climate, from June/2011 to April/2013, in ﬁve sites of Sao Paulo State, Brazil, for 8 consecutive exposure periods of 12 weeks each. The levels of essential and non-essential elements, including trace metals, were quantiﬁed at the end of each exposure. T. usneoides and A. fasciata indicatedN, Fe, Zn, Co, Cr, and V as air contaminants in the studied sites, during wet and dry seasons and both species were recommended for qualitative biomonitoring. Concentration levels of N, Ca, S, Fe, Zn, Cu, B,Co, and Ni were signiﬁcantly higher in T. usneoides than in A. fasciata. However, A. fasciata showed a higher effective retention capacity of Ni, Pb, V, Cu, Fe, Cr, and Co during ﬁeld exposure, as indicated by the estimate of enrichment factor relative to basal concentrations. This species is more suitable for detecting the atmospheric pollution level of those metals than the T. usneoides. Both species indicated adequately the seasonal differences in the pollution levels of several elements, but T. usneoides presented higher ability for biomonitoring the spatial variations and for indicating more properly the sources of each element in the studied region than the A. fasciata.